Biomimetic Metal−Organic Frameworks as Targeted Vehicles to Enhance Osteogenesis. Issue 12 (4th March 2022) - Liang, Na; Ren, Na; Feng, Zhichao; Sun, Zhaoyang; Dong, Mengwei; Wang, Wenhan; Liu, Feng; Sun, Chunhui; Zhou, Weijia; Xing, Zhiqing; Wang, Jingang; Liu, Chao; et al.
Abstract: Although engineered nanoparticles loaded with specific growth factors are used to regulate differentiation of stem cells, the low loading efficiency and biocompatibility are still great challenges in tissue repair. A nature‐inspired biomimetic delivery system with targeted functions is attractive for enhancing cell activity and controlling cell fate. Herein, a stem cell membrane (SCM)‐wrapped dexamethasone (DEX)‐loaded zeolitic imidazolate framework‐8 (ZIF‐8) is constructed, which integrates the synthetic nanomaterials with native plasma membrane, to achieve efficient DEX delivery and DEX‐mediated bone repair. The DEX@ZIF‐8‐SCM enables high DEX loading capacity, modulates the sustained release, and facilitates the specific uptake of mesenchymal stem cells (MSCs), owing to the porous property of ZIF‐8 and the innate targeting capability of SCM. The endocytosed DEX@ZIF‐8‐SCM shows high cytocompatibility and greatly enhances the osteogenic differentiation of MSCs. Furthermore, RNA‐sequencing data reveal that the phosphoinositide 3‐kinase (PI3K)‐Akt signaling pathways are activated and dominantly involved in the accelerated osteogenesis. In the bone defect model, the administrated DEX@ZIF‐8‐SCM exerts excellent biocompatibility and effectively promotes bone regeneration. Overall, the SCM‐derived biomimetic nanoplatform achieves targeted delivery, excellent biosafety, and enhanced osteogenic differentiation and bone repair, which provides a new and valid strategy for treating various tissue injuries. Abstract : A biomimetic delivery system is constructed by encapsulating dexamethasone (DEX)‐loaded zeolitic imidazolate framework‐8 (ZIF‐8) with a stem cell membrane (SCM). Owing to the porous structure of ZIF‐8 and the innate targeting capability of SCM, the DEX@ZIF‐8‐SCM enables high DEX loading capacity and specific delivery to stem cells. Furthermore, the nanoplatform exerts superior capacity of enhancing osteogenic differentiation and bone regeneration.